Kecakapan Bertindak Penyandang Disabilitas Autisme Menurut Hukum Perdata - Abdul Hariss; Nur Fauzia (Universitas Batanghari Jambi, 2021)
A person with a disability has the right to be treated the same as other human legal subjects. Therefore, the government is obliged to realize the rights listed in the convention, using laws and regulations, including how to fulfill the rights of persons with disabilities in every aspect of life such as: a decent living, education, health and so on, just like humans who live with disabilities. other normal. An autistic person or what in psychological terms is called autism, is included in the category of a person with a mental disability. A person is said to be autistic if he experiences abnormalities in carrying out a legal act, development in terms of the quality of the ability to carry out social and emotional relationships in the social environment of the community. A person is said to have autism, namely someone who has a special character in people generally not by showing mental (psychic), emotional (affective) or physical (physical) disabilities. The word autism, namely